Extraction of HCV-RNA from Plasma Samples: Development towards Semiautomation - Imran Amin; Tania Jabbar; Fawad Niazi; Muhammad Saeed Akhtar (International Journal of Analytical Chemistry)
A semiautomated extraction protocol of HCV-RNA using Favorgen RNA extraction kit has been developed. The kit provided protocol was modified by replacing manual spin steps with vacuum filtration. The assay performance was evaluated by real-time qPCR based on Taqman technology. Assay linearity was confirmed with the serial dilutions of RTA (Turkey) containing 1 × (106, 105, 104, and 103) IU mL−1. Comparison of test results obtained by two extraction methods showed a good correlation (r=0.95, n=30) with detection limit of 102 IU mL−1. The semiautomated vacuum filtration based protocol demonstrated high throughput: 35 minutes for the extraction of a batch of 30 samples (150 µL each) with reduced labor, time, waste, and cost. Performance characteristics of semiautomated system make it suitable for use in diagnostic purpose and viral load determinations.